CULTURE AND BUILT ENVIRONMENT A THEORITICAL PERSPECTIVE - I Made Sukadana (Bumi Lestari Journal of Environment, 2009)
Culture is affected by the environmental demands, and culture influences what people do toward the environment. What remarkable is that culture and environment influenced each other. They are frequently responsive to the demands of the environment. Furthermore, culture influences people in shaping built environment such as, cities, villages, houses, and farms. Culture influences environment through travelling, commerce, mass media, and missionaries of religion. Contact among other people, ideas and traditions effected cultural change. As a result; people are able to do contextualization that is reject, adopt, and accept the previous culture and it affected the built environment arrangement.